LEGAL ANALYSIS CONCERNING GOOD GOVERNANCE AND CONFLICT OF INTEREST OF THE NOMINATION COMMITTEE FOR UNIVERSITY PRESIDENT OF THE RAJABHAT UNIVERSITIES - Tibwongsa, Pinyapat; Saksang, Sitthikorn (Academic Journal Phranakhon Rajabhat University, 2022)
Regarding the provision of laws on the appointment of nomination committee from the university council committee, if the committee appoints the nomination committee in accordance with the legal framework under Section 18, Section 28 and Section 29, the Rajabhat University Act, B.E. 2547 (2004), such appointment isn’t against the good governance according to Section 9, the Higher Education Act, B.E. 2562 (2019). However, there is an arguable issue concerning the nomination committee from the representatives of the university council committee to nominate and appoint the university president as being an interested party under the Administrative Procedure Act, B.E. 2539(1996), Section 13. The disputant according to Section 13 concerns the nomination committee for the university president has the right to oppose the council committee’s consideration under Section 15 and the council committee has the right to oppose the nomination committee’s consideration under Section 16. The opposition against the council committee’s consideration could be brought to the administrative court to revoke the university council’s resolution.